Improving blast segmentation of acute myelogenous leukaemia (AML) images using bright stretching technique - Aimi Salihah, Abdul Nasir; Mohd Yusoff, Mashor, Prof. Dr.; Azian Azamimi, Abdullah (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.